Exploration of the Shared Gene and Molecular Mechanisms Between Endometriosis and Recurrent Pregnancy Loss - Ye, Zhuang; Meng, Qingxue; Zhang, Weiwen; He, Junli; Zhao, Huanyi; Yu, Chengwei; Liang, Weizheng; Li, Xiushen; Wang, Hao (Frontiers in Veterinary Science, 2022)
Endometriosis (EMs) is a common benign gynecological disease in women of childbearing age, which usually causes pelvic pain, secondary dysmenorrhea and infertility. EMs has been linked to recurrent pregnancy loss (RPL) in epidemiological data. The two's relationship, however, remains unknown. The purpose of this study is to explore the underlying pathological mechanism between EMs and RPL. We searched the Gene Expression Comprehensive (GEO) database for data on EMs and RPL. Co-expression modules for EMs and RPL were investigated using weighted gene co-expression network analysis (WGCNA). Search for common genes based on the module's and disease's correlation. For bioinformatics analysis of common genes, the "R" programming language was employed. MicroRNAs (miRNA) and their corresponding target genes linked to EMs and RPL were found using the Human MicroRNA Disease Database (HMDD) and the miRTarbase database. Finally, we constructed miRNA-mRNA regulatory networks connected to the two disorders using the intersection of target genes and shared genes. Three and two modules were discovered as significant modules for EMs and RPL, respectively, by WGCNA. The energy metabolism route might be a common pathogenic mechanism of EMs and RPL, according to the findings of a KEGG enrichment analysis. We discovered a number of target genes that may be linked to these two disorders, as well as the potential mechanism. RAB8B, GNAQ, H2AFZ, SUGT1, and LEO1 could be therapeutic candidates for RPL and EMs. The pathogenic process of EMs and RPL may be linked to the PI3K-Akt signaling pathway and platelet activation. Our findings revealed the underlying pathological mechanism of RPL secondary to EMs and identified many useful biomarkers or therapeutic targets. point genes.